THE VOICE WITHIN: ADULT LARYNGOMALACIA AS A RARE COMPLICATION OF ACROMEGALY - Menon, Saieehwaran; Ooi, Xin Yi; Lim, Sue Wen; Wong, Hui Chin; Yong, Sy Liang; Ng, Chong Sian (Journal of the ASEAN Federation of Endocrine Societies, 2025)
INTRODUCTION/BACKGROUND Acromegaly is a chronic disorder caused by excess growth hormone (GH) and insulin-like growth factor 1 (IGF-1), most often due to a GH-secreting pituitary adenoma. Adult-onset laryngomalacia is rarely reported. CASE A 69-year-old male with a history of hyperthyroidism and colon cancer presented with progressive left eye blurring. He was initially treated for herpetic keratouveitis. During follow-up, coarse facial features suggestive of acromegaly—thickened skin, enlarged jaw, tongue, hands, and feet—were noted. He had noisy breathing, prompting ENT referral. Flexible laryngoscopy revealed redundant mucosa over the arytenoids prolapsing into the laryngeal inlet during inspiration, consistent with adult-onset laryngomalacia. Biochemical evaluation confirmed acromegaly (GH >50 ng/mL; IGF-1: 973.5 ng/mL) with secondary hypogonadism. MRI showed a 1.6 × 2.2 × 1.6 cm pituitary macroadenoma compressing the left optic nerve. He was started on intramuscular Octreotide LAR and underwent supraglottoplasty. Laryngomalacia is typically a pediatric condition caused by dynamic supraglottic collapse during inspiration. In adults, it is uncommon and may result from structural abnormalities or acquired soft tissue redundancy, as seen in acromegaly. Chronic GH and IGF-1 excess leads to hypertrophy of soft tissues, including the larynx, epiglottis, aryepiglottic folds, and arytenoids, contributing to narrowing of the upper airway. Awake fiberoptic laryngoscopy is the diagnostic gold standard. Findings include inspiratory collapse of supraglottic structures, which may cause stridor, dysphonia, or sleep-disordered breathing. In acromegaly, cartilage overgrowth and mucosal thickening reduce airway diameter and alter tissue compliance. The hyoepiglottic ligament may also lose tensile strength, further predisposing to dynamic airway obstruction. Laryngomalacia may be misdiagnosed or attributed to obstructive sleep apnea, a common comorbidity in acromegaly and distinct anatomical distortion should prompt ENT evaluation. CONCLUSION Laryngomalacia should be considered in acromegalic patients presenting with stridor or noisy breathing. Early recognition and surgical management can prevent airway complications and improve patient outcomes.